AI-copywrite and AI-rewrite for textual content creation of corporate websites: linguistic aspect and new challenges - Seidekhanov, С.А.; Dossanova, А.М.; Raisova, А.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The article is dedicated to analyzing the use of artificial intelligence (AI) in copywriting and rewriting, examining its linguistic features and impact on textual content. It discusses the advantages and disadvantages of AI-generated texts, their lexical, grammatical, and stylistic characteristics, as well as a comparative analysis with texts written by humans. Special attention is given to ethical issues related to authenticity, authorship, and the influence of AI on linguistic culture. The article also explores new challenges for copywriters and the impact of AI on the job market.